Effect of Different Concentration of Plant Growth Regulators on 𝙄𝙣 𝙑𝙞𝙩𝙧𝙤 Culture of 𝙆𝙖𝙚𝙢𝙥𝙛𝙚𝙧𝙞𝙖 𝙨𝙞𝙨𝙖𝙠𝙚𝙩𝙚𝙣𝙨𝙞𝙨 Picheans.& Koonterm - Thungjan, Rattiya; Saensouk, Surapon; Saensouk, Piyaporn (Burapha Science Journal, 2024)
Background and Objectives : This research studied a propagation protocol of Kaempferia sisaketensis Picheans. & Koonterm which is a rare and endemic plant of The Northeast of Thailand using plant tissue culture techniques. Methodology : Microshoot (1 cm long) of K. sisaketensis were cultured on Murashige and Skoog medium (MS) supplemented with various concentrations of cytokinins (BA, kinetin, and TDZ) and auxin (NAA) for eight weeks. Transferring complete plantlets of K. sisaketensis to pots containing soil, sand and soil:sand (1:1) under greenhouse conditions for eight weeks. Main Results : The results show that culturing the microshoot of K. sisaketensis on MS medium supplemented with 1 mg/l kinetin produced the highest number of shoots, which is 5.30 shoots/explant. For root induction, the results show that the highest number of roots were 14.50 roots/explant when microshoots of K. sisaketensis was cultured on MS medium augmented with 2 mg/l kinetin and 1 mg/l NAA. After transferring complete plantlets of K. sisaketensis to pots containing different types of planting materials under greenhouse conditions for eight weeks, the best survival rate was 100% when transplanting to sand. Conclusions : This research is the first report on tissue culture of K. sisaketensis. This study can be used to propagate and preserve K. sisaketensis from extinction.